Changes in the organ of vision in neurofibromatosis type 1 in the developmental age - Mirosława Grałek; Katarzyna Piasecka; Katarzyna Wasyliszyn-Sieroszewska; Anna Niwald (Klinika Oczna)
Neurofibromatosis type 1 is a genetic disorder with clinical manifestations determined by their origin in the three germ layers. Globally, the prevalence of neurofibromatosis type 1 is estimated at 1 : 3,000 to 1 : 3,500. Clinical manifestations include both systemic and vision-related changes. Systemic disorders in affected children include primarily neurofibromatas manifesting as hamartoma, located in the skin, in various internal organs, and in the organ of vision. Ocular manifestations mainly present as eyelid abnormalities due to hamartomas, Lisch nodules on the iris, optic glioma, and glaucoma. Diagnostics relies on clinical and imaging evaluations, as well as genetic testing. There is no causal treatment. The therapeutic management depends on each patient’s specific needs. Children with neurofibromatosis type 1 with ocular lesions require regular ophthalmic care.